Combination of valproate and paroxetine in mice exposed to picrotoxin - Kamal SM (Dove Medical Press, 2012)
Sahar M KamalDepartment of Pharmacology, Faculty of Medicine, University of Ain-Shams, Cairo, EgyptAbstract: The frequent coexistence of depression in epileptic patients raises the issue of simultaneous use of antidepressants along with antiepileptic drugs in the management of such cases. However, it is necessary to evaluate the safety of these antiepileptic/antidepressant drug combinations. The present study investigates the effect of the antidepressant paroxetine (a selective serotonin reuptake inhibitor) administered alone or in combination with the antiepileptic drug sodium valproate on chemoconvulsions induced by picrotoxin (PTX). Seizure score was recorded in vivo, and the levels of thiobarbituric acid-reactive substances and gamma aminobutyric acid (GABA) were measured in the nucleus accumbens of the tested groups of mice. The results show enhancement of seizure severity with significant reduction in GABA levels upon PTX treatment that were reversed by its combination with sodium valproate. On the other hand, paroxetine administered in combination with sodium valproate provided significant protection against PTX-induced convulsions as well as a significant increase in GABA levels in selected brain areas. These results favor their application in management of epilepsy-depression comorbidities.Keywords: valproate, paroxetine, GABA, nucleus accumbens, albino mice